Plants Inspired Biomimetics Architecture in Modern Buildings: A Review of Form, Function and Energy - Maryam Bijari; Ardalan Aflaki; Masoud Esfandiari (Biomimetics)
Biomimicry architecture provides innovative solutions to contemporary environmental challenges by drawing inspiration from nature’s strategies to enhance sustainability and energy efficiency in the built environment. Plants, with their remarkable ability to adapt to changes in light, temperature, and humidity, serve as a central model for biomimetic design due to their potential to optimize energy use and improve building performance. By leveraging these natural principles, biomimetic architecture can significantly reduce carbon emissions and create eco-friendly structures that respond dynamically to environmental conditions. This approach not only addresses the urgent need for sustainable development but also fosters harmony between human-made environments and the natural world. This study offers a comprehensive review of biomimetic technologies, focusing on their role in improving energy efficiency and building performance. Also, it examines a range of global case studies that have successfully implemented biomimicry, showcasing its versatility and effectiveness across diverse environmental and architectural contexts. Based on these insights, this research proposes a novel design inspired by the moonflower plant, which adapts to its environment by responding to external stimuli. The proposed design applies these adaptive strategies to architectural solutions, enabling buildings to optimize performance by dynamically interacting with environmental conditions such as light and temperature. By analyzing biomimetic principles and their applications, this study contributes to the growing body of knowledge on sustainable architecture. It highlights the potential of biomimicry to balance environmental sustainability with economic growth, offering valuable insights for architects, designers, and policymakers seeking to create greener, more efficient built environments.